On either side of the levee: exploring social and ecological benefits of adaptive flood resilience strategies - Mueller, Abigail (Kansas State University, 2024)
With increasing urbanization and threats from climate change, urban flooding has become a prevalent issue, leading to a growing reliance on levees along many river cities. While urban levees are an essential measure of protection in many of these communities, they often disconnect people from access to the river and can have detrimental effects on natural floodplain ecosystems. The city of Manhattan, Kansas has experienced several major flood events in recent decades and is pursuing a project which includes several upgrades to the levee, including raised walls, improved relief wells, and structural reinforcements. Even with the coming levee improvements, alternative methods should be explored to mitigate further flood damage, improve human connection with the waterfront, and restore natural floodplain ecosystems. Thus, this study examines both the social and ecological aspects of levee design by asking the following question: “How can levees be reimagined to enhance flood resilience, ecological function, and community access to the riverfront?”. This, along with several related sub-questions, is answered by (1) developing a framework for levee design analysis through a comprehensive synthesis of literature; (2) using survey methods to assess community members’ perception of river access before and after design interventions; and (3) proposing an adaptive levee design strategy for the city of Manhattan, Kansas that provides ecological and social benefits in addition to mitigating the risk of urban flooding. The study contributes to the body of work in landscape architecture through the exploration of innovative strategies to produce an improved levee design that combines traditional typologies with more creative, nature-based adaptations and enhances human experience.
Keywords: Ecological levee design; Ecosystem services; River-society interactions; Flood resilience